Age-Dependent Neuropsychiatric Symptoms in the NF-κB/c-Rel Knockout Mouse Model of Parkinson’s Disease - Parrella, Edoardo; Del Gallo, Federico; Porrini, Vanessa; Gussago, Cristina; Benarese, Marina; Fabene, Paolo Francesco; Pizzi, Marina (Frontiers in Behavioral Neuroscience, 2022)
Non-motor symptoms are frequently observed in Parkinson's disease (PD) and precede the onset of motor deficits by years. Among them, neuropsychiatric symptoms, including anxiety, depression and apathy, are increasingly considered a major challenge for PD patients and their caregivers. We recently reported that mice lacking the NF-κB/c-Rel protein (c-rel-/- mice) develop an age-dependent PD-like pathology and phenotype characterized by the onset of non-motor symptoms, including constipation and hyposmia, starting at 2 months of age, and motor deficits at 18 months. In order to assess whether c-rel-/- mice suffer also from neuropsychiatric symptoms, in this study we tested different cohorts of wild type and c-rel-/- mice at 3, 6, 12 and 18-20 months with different behavioral tests. Mice lacking c-Rel displayed anxiety and depressive-like behavior starting in the premotor phase at 12 months, as indicated by the analysis with the open field test and the forced swim test with water wheel, respectively. Apathetic behavior, investigated with the nesting building test, was detected at 18-20 months. Taken together, these results indicate that c-rel-/- mice recapitulate the onset and the progression of PD-related neuropsychiatric symptoms. Therefore, this animal model may represent a valuable tool to study the prodromal stage of PD and for testing new therapeutic strategies to alleviate neuropsychiatric symptoms.